Atropine Premedication Facilitates Ultrasound-Guided Reduction by Saline Enema in Children With Intussusception - Liu, Xiao; Xia, Bei; Yu, Hong-kui; Hu, Lie-zhen; Fan, Shu-min; Xiao, Dong; Gu, Li-xian; Chen, Jia-kun; Wen, Zhi-bo; Ma, Xiao-peng (Frontiers in Pharmacology, 2019)
Background and objective: Intussusception is the most frequent pediatric abdominal emergency. Intestinal spasm, ischemia, necrosis and even death may occur without prompt diagnosis and treatment. The ultrasound-guided reduction by saline enema is a preferred non-surgical procedure for intussusception. Muscular relaxants can relieve the intestinal spasm and edema by relaxing the intestinal smooth muscle, which may facilitate the treatment of intussusception. However, controversy persists on whether muscular relaxants are effective in the procedure. Therefore, the purpose of our study was to assess the efficacy of atropine known as a muscular relaxant in ultrasound-guided reduction by saline enema in children with intussusception. Methods: All patients with intussusception diagnosed and treated in our department from July 2016 to February 2018 were included. Four hundred and thirty-seven children were enrolled and randomly divided into two groups: an atropine group and a control group. Intramuscular atropine at a dose of 0.02mg per kilogram of body weight was administrated 15 minutes before ultrasound-guided reduction by saline enema in the atropine group. In the control group, the ultrasound-guided reduction was performed without using any muscular relaxants. The success rate, duration of the reduction, volume of saline, maximum intra-rectal pressure and complications were recorded and compared between the two groups. Results: The success rate was 95.9% (212 out of 221) and 94.9% (205 out of 216) in the atropine group and the control group, respectively. No significant difference was observed in the success rate between the two groups (P>0.05). The duration of reduction was significantly lower in the atropine group than in the control group (P<0.01). The volume of saline was also significantly lower in the atropine group than in the control group (P<0.05). The maximum intra-rectal pressure showed no difference between the two groups (P>0.05). Conclusions: Atropine premedication can facilitate ultrasound-guided reduction by saline enema in children with intussusception, by reducing the duration of reduction and the volume of saline in the procedure.